10.61533 ANALISIS PENERAPAN DASAR PENCATATAN AKUNTANSI PADA UMKM SEMBAKO DIDUSUN III SERDANG DESA JELUTUNG II KECAMATAN SIMPANG RIMBA - Alis Sakti Wangi; Hendarti Tri Setyo Mulyani; Medinal (Jurnal Ilmiah Niaga Bisnis Elektronik, 2026)
This research was conducted at one of the Micro, Small and Medium Enterprises in Hamlet III Serdang, Jelutung II Village, Simpang Rimba District. The Grocery Business is the object of this research. The purpose of the research is to determine the extent of the suitability between the basic concepts of accounting, accounting cycles and financial accounting standards of micro, small and medium entities with the application of accounting carried out in the Grocery Business in Hamlet III Serdang, Jelutung II Village, Simpang Rimba District. The data that has been collected is then analyzed using Descriptive Qualitative Method, Data Collection Technique by means of interviews, documentation and observation. Based on the results of research and data analysis it can be concluded that the recording carried out by basic food entrepreneurs is not in accordance with the Basic Concepts of Accounting including the concept of business unity which still combines household finances with business finances, the basic concept of recording using cash basis recording, the matching concept does not calculate costs included in business activities in the calculation of profit and loss, the concept of business continuity recording and calculating depreciation on fixed assets is not included in the calculation of profit and loss, and the concept of time periods regarding reporting periods for business progress with several basic concepts of accounting that have not been implemented, business actors have also not fully implemented the accounting cycle and Financial Accounting Standards for Micro, Small and Medium Entities (SAK EMKM).